Improvement of take-away water cup design by using concurrent engineering approach - Siti Mahfuzah, Mohamad (2012)
This final year project is about improvement of take-away water cup design by using concurrent engineering approach. Take-away water cup is widely used in fast food restaurant, the customer demand to satisfy when using this product. It is because, customers is still become more and more demanding and require being the product improved in all the time. Although the take-away it is look perfect but it is still have drawback. The problem is what possible improvements of take-away water cup are and how to match voice of customer with technical description in order for improving the cup design. To proceed the project, there are several method use to get voice of customer through interviewing, analyze QFD (Quality function deployment) tool, design the product by using CAD drawing, and lastly fabricate the product by using rapid prototyping. QFD is one of the tools in concurrent engineering (CE). QFD is a system to deploy the voices of the customers in understanding their requirements into the appropriate technical requirements for each stage of product development and production. Based on the result and discussion, after analyzing the QFD, it shows that customer really need to improve the cover of the cup by adding tip on the cover in order for easy to drink and make a hole for easy to mix between sugar or creamer with the hot coffee. Finally, product prototyping of take-away water cup is demonstrated and manufactured based on market survey and QFD analysis.